(untitled) - Wild, John J. (New York, 2013)
With 55 years of success in the principles of accounting market, Fundamental Accounting Principles, 21E by Wild, Shaw and Chiappetta has endured and adapted to changes in accounting, technology, and student learning styles. Its innovation is reflected in its extensive use of small business examples, the integration of new technology learning tools, superior end-of-chapter material, and a highly engaging, pedagogical design. Inclusion of Connect, Connect Plus and QuickBooks application software provides students every advantage as they strive to understand the key concepts of accounting and their role in business.
Keywords: Accounting,Kế toán